1999
DOI: 10.1557/jmr.1999.0171
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Preferred Orientation of Pt Thin Films Deposited by dc Magnetron Sputtering Using Ar/O2 Gas Mixtures

Abstract: 200)-oriented Pt thin films were deposited on SiO 2 ͞Si substrates by dc magnetron sputtering using Ar͞O 2 gas mixtures. Oxygen incorporation into Pt films changed deposition rate, resistivity, stress, and preferred orientation of the films. Increase in film resistivity and decrease in tensile stress were presumed to be the results of the incorporated oxygen into grain boundaries, while the change of preferred orientation resulted from the oxygen incorporation into the Pt lattice. The preferential growth of (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The latter involves normal grain growth where all existing grains grow uniformly, as well as abnormal grain growth (also known as secondary crystallization), where one type of grain will grow significantly faster than the others driven by the difference in surface energies between different grain orientations. Our data show that such abnormal growth in Pt is significantly enhanced by the presence of borazine. For Pt thin films it has been frequently observed that the presence of oxygen is detrimental to the formation of grains with (111) surface orientation. , In this context B, which can readily adsorb in Pt grain boundaries, is frequently used as deoxidizer, and the addition of B to Pt has been seen to cause GB unpinning . We therefore attribute the accelerated abnormal Pt grain growth to GB unpinning via removal of pre-existing solutes.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The latter involves normal grain growth where all existing grains grow uniformly, as well as abnormal grain growth (also known as secondary crystallization), where one type of grain will grow significantly faster than the others driven by the difference in surface energies between different grain orientations. Our data show that such abnormal growth in Pt is significantly enhanced by the presence of borazine. For Pt thin films it has been frequently observed that the presence of oxygen is detrimental to the formation of grains with (111) surface orientation. , In this context B, which can readily adsorb in Pt grain boundaries, is frequently used as deoxidizer, and the addition of B to Pt has been seen to cause GB unpinning . We therefore attribute the accelerated abnormal Pt grain growth to GB unpinning via removal of pre-existing solutes.…”
Section: Resultsmentioning
confidence: 92%
“…For Pt thin films it has been frequently observed that the presence of oxygen is detrimental to the formation of grains with (1 1 1) surface orientation. 51,55 In this context B, which can readily adsorb in Pt grain boundaries, 56 is frequently used as deoxidizer, 57 and the addition of B to Pt has been seen to cause GB unpinning. 54 We therefore attribute the accelerated abnormal Pt grain growth to GB unpinning via removal of pre-existing solutes.…”
Section: Details Of Growth Processmentioning
confidence: 99%
“…Advanced techniques exist to improve film adhesion such as ion-beam mixing [199]. It is also possible to promote adhesion of a Pt film directly on the SiO 2 substrate by sputtering the Pt in an Ar-O 2 mixture [200]. However, for Pt on SiO 2 , useful adhesion is commonly achieved by inserting an intermediate glue layer between the Pt and SiO 2 .…”
Section: Adhesion Layers For Pt On Siomentioning
confidence: 99%
“…A silicon wafer (LG siltron Inc., Korea) was used as the solid support and gold (Au) was sputtered to the silicon substrate with a thickness of 43 nm after chromium (Cr) sputtering as an adhesion material with a thickness of about 2 nm [19]. The sputtered Au substrate was cleaned using piranha solution composed of 30 vol% H 2 O 2 (Sigma-Aldrich, MO, USA) and 70 vol% H 2 SO 4 (Duksan Chemical Co. Ltd., Korea) at 60 1C for 4 min [20].…”
Section: The Immobilization Of Au Nanoparticle On Odt Sammentioning
confidence: 99%